Specificities of potential and trends of economic development of Krasnokutsk territorial community: a human-geographical vision - Maliarenko, Kostiantyn (Human Geography Journal, 2025)
In the context of full-scale war and the ongoing decentralization reform, Ukraine’s territorial communities have faced unprecedented challenges that require a rethinking of the mechanisms for utilizing their internal potential. For the communities of the Kharkiv region, particularly the Krasnokutsk settlement territorial community, the issue of economic resilience is of particular importance due to the proximity to the combat zone, the transformation of budget flows, and the need to adapt the local economy to crisis conditions. Socio-geographical analysis allows for a comprehensive assessment of the resource base and dynamic changes in the community’s life, which is essential for developing effective recovery strategies. The purpose of the article is to identify the specificities of the potential and establish the trends of economic development of the Krasnokutsk territorial community, and to substantiate promising directions for strengthening economic resilience in modern conditions. A complex of methods was used: systemic-structural analysis to study the components of the potential; statistical and comparative methods to assess the dynamics of the community’s financial indicators; and SWOT analysis to identify strengths, weaknesses, opportunities, and threats to the community’s development. It was established that the potential of the Krasnokutsk settlement territorial community is based on a unique combination of the agro-industrial sector (hydrocarbon extraction, agriculture) and the high recreational value of the territories (nature reserve fund sites). A trend towards a decrease in the community’s financial autonomy in 2024 was revealed due to legislative changes and military risks, which necessitates the diversification of the economy. It is proven that despite demographic losses and migration challenges, the community demonstrates a high level of adaptability. Priority development vectors were identified: the transition from a raw material model of the agricultural sector to a processing one, the capitalization of the nature reserve fund through the development of ecotourism, and the implementation of energy-efficient technologies in the municipal sphere.